EFFICACY OF IN-VITRO MATURATION OF BUBALINE OOCYTES IN TCM 199, TCM 199 + PMSG AND FOLLICULAR FLUID - KULASEKAR, T; RAJU, K G SOLMON; SADASIVA RAO, K (The Indian Journal of Animal Reproduction, 2023)
A total number of 498 ovaries were procured from municipal slaughter house, Hyderabad. The ovaries were subjected to slicing, aspiration and post aspiration slicing in order to retrieve the oocytes. The oocyte retrieval rate was 73.68, 43.61 and 47.91 per cent in slicing , aspiration and post aspiration slicing methods, respectively. The oocyte recovery per ovary was 2.91, 1.53 and 1.89 in slicing, aspiration and post aspiration slicing, respectively. Retrieved oocytes were graded into A, B, C and D based on cellular investment and homogeneity. The yield of grade A oocytes were 53.92, 42.57 and 46.72 in slicing, aspiration and post aspiration slicing techniques, respectively. The yield of grade B oocytes was 28.87, 20.92 and 29.10, respectively. The yield of grade C and D oocytes were 15.69 and 9.52; 11.27 and 11 .24; and 13.93 and 10.25 in slicing, aspiration and post aspiration slicing methods, respectively. The A, B and C graded oocytes were matured in TCM 199, buffalo follicular fluid (bu FF) alone and TCM 199 supplemented with PMSG. Based on the degree of cumulus expansion, the maturation was classified as DO, D1 and D2 cumulus expansion. Significantly higher per cent of grade A and B oocytes attained D2 and D1 degree of cumulus expansion while significantly higher per cent of C grade oocytes retained in DO degree of cumulus expansion. The per cent of grade A oocytes extruded first polar body was 70.83, 5.55 and 42.50 in PMSG, bu FF and TCM 199 media, respectively Higher per cent of oocytes could be harvested by post aspiration and slicing technique and commercially available PMSG could be supplemented to TCM 199 media for invitro-maturation of follicular oocytes.